Improving anti-oxidation properties of metal interconnects in solid oxide fuel cells via a dense Ag-based coating layer - Yang, Gongmei; Potter, Andrew; Sumner, Joy (Elsevier, 2026)
Solid Oxide Fuel Cells (SOFCs) are a highly efficient energy conversion technology, but the degradation of metal interconnects remains a critical challenge. Conventional coatings often lack sufficient electrochemical performance and stability. In this study, a dense Ag coating was developed using the screen-printing method to improve the electrochemical performance and chemical compatibility of SOFC interconnects. Symmetric and single cells were prepared with La0.6Sr0.4Co0.2Fe0.8O3−δ cathodes and SUS430 interconnects to evaluate the coating under high-temperature conditions, simulating real SOFC operation. The Ag coating demonstrated excellent adhesion, uniformity, and oxidation resistance, with conductivity increasing from 0.01 to 13.13 S cm^−1 at 650 ∘C after coating and the area-specific resistance decreasing from 1.843 to 0.378 Ω cm^2 after coating between cathode and interconnect at 750 ∘C. Moreover, the coating effectively inhibited Cr diffusion from the interconnect to the cathode, addressing a major limitation in SOFC durability. These results suggest that Ag coatings offer a practical and promising solution to enhance the performance and extend the lifespan of SOFC systems.
Keywords: Solid oxide fuel cells; Metallic interconnects; Ag coating; Oxidation; Cr poisoning; Energy; 4004 Chemical engineering; 4012 Fluid mechanics and thermal engineering; 4019 Resources engineering and extractive metallurgy